Arsenic removal using silver-impregnated Prosopis spicigera L. wood (PSLW) activated carbon: batch and column studies - M Murugan; M Jansirani; P Subramaniam; E Subramanian (Journal of Applied Sciences and Environmental Management, 2018)
Silver-impregnated carbon (SIC) and its precursor (un-impregnated) derived from an easily available low cost plant material Prosopis spicigera L. wood (PSLW) carbon was investigated for their ability to remove arsenic from aqueous solutions in batch and column experiments. Arsenic uptake has no regular trend with increasing pH; contains two adsorption maxima, the first adsorption maximum at pH 4.0 and a second adsorption maximum at pH 10.0. The extent of As (III) removal increased with increase in temperature. As (III) sorption kinetics was well fitted by pseudo second order with pore diffusion as rate determining step. The applicability of Langmuir isotherm suggests the formation of monolayer coverage of As (III) at the outer surface of the adsorbent. Thermodynamic parameters show that the adsorption was spontaneous and endothermic in nature. Column experiments were done using Thomas model, the maximum adsorption capacity of SIC was found to be 9.36 mg/g.